Sekolah Sebagai Sistem Budaya dalam Transformasi Pendidikan - Dhiyaulrizq, Ghina Azhzhahra; Wulandari, Fitri; Hajrani, Hajrani; Nur, Hasruddin (Indo-MathEdu Intellectuals Journal, 2026)
Educational transformation in the modern era demands systemic changes that not only focus on the curriculum or technology but also on the culture that binds all components of the school. This article aims to analyze how schools function as a cultural system in the process of educational transformation. The research method used is a qualitative-descriptive study with a literature review approach on organizational culture theory, educational ecology theory, and educational transformation theory. The sources of data for this study include academic books, articles in national and international journals, as well as policy documents and international reports. Data analysis was carried out using content analysis with stages of data reduction, concept categorization, and interpretative analysis. The study results indicate that schools have a character as cultural systems marked by values, norms, symbols, habits, and social practices that shape the institution's identity. Educational transformation will be effective if changes encompass cultural aspects, including leadership patterns, social relationships, learning practices, and adaptation to technology. This study emphasizes that structural changes without cultural change only result in superficial transformation. The article implies that policymakers and schools need to reorganize the paradigm of change by placing culture as the main foundation of educational transformation